The Study of Baccilus Cereus on Surface Plasmon Resonance Based Biosensor - Priyadarshini, Rashmi; Narayanappa, C K (International Journal of Engineering and Technology, 2018)
SPR biosensors have obtained elaborate application in the area of biological interactions and detection for chemo-bio analytes, where the benefits of real-time, label attraction potential and label-free technique are prominent. SPR techniques are implementing. Non-Invasive biomolecule monitoring by using blood samples from the body. Sensor development involves high sensitivity. Of them all, the SPR configurations with waveguide coupling has a waveguide mode and surface plasma mode, coupled via an evanescent field in scattered manner thus providing superior control on the reaction and can ultimately lead to superior sensitivity and additionally promote loosely diversified, multichannel and swift stimuli devices construction, capable of distinguishing particular sensor responses from random response and capable of concurrent detection of many analytesin analogy to waveguide coupled configuration which being heavy. With the above requirements our present work puts limelight on sucha multi waveguide integrated optical based SPR biosensor. This paper presents a unique work of analyzing the bacterial content in human blood sample with respect to water and protein as immersion layers. Results include analyzing the simulation results with patterns of waveform and frequency for individual B. cereus var. mycoides and B. megaterium bacteria respectively.